Pendampingan Dan Pengembangan Umkm Di Kelurahan Kepanjenlor Kota Blitar Melalui Re-Branding Dan Integrated Marketing Communication (IMC) - Isna Agustina Safira; Mu’tasim Billah; Muhammad Nashir Hasan; Aura Arindra Ramadhani; Annisa’ Laras Atie; Lintang Aji Arroziqi; Ira Wikartika; Muhammad Ahmi Husein (Literasi: Jurnal Pengabdian Masyarakat dan Inovasi, 2022)
Re-Branding is an effort by a company to change and re-new their brand, with the intention to make it better. Re-branding does not ignore the initial goal of its company, which is profit-oriented. IMC is the approach that makes sure a communication of the brand is conformable for your marketing channel. The purpose of this service is to promote digitally and help the product development in order to increase the quality. The methods that are used in this service are observing the UMKM, designing logo with supergraphic, and conceiving the design of UMKM product inovation. The result of this service is the increase of enthusiasm of the UMKM in Kepanjenlor village, Kepanjen Kidul Sub-District, Blitar city. They are excited in the process of rebranding and IMC.